Zum terminologischen Status der Inkorporation in der deutschen und der dänischen Wortbildungsbeschreibung - Stopyra, Janusz (Folia Scandinavica Posnaniensia, 2016)
The article deals with the subject of incorporation shown as a special kind of composition and derivates formed from phrases (Zusammenbildungen). The author attempts to differentiate between these two types and also describes such phenomena as predicateargument-structure and the principle of the meaningful word. In his opinion it is worth using such terms to give the language description a better overview.